Building a Culture of Patient-Centered Care and Its Impact on Hospital Performance - Polla, Johanes; Prabowo, Harjanto; Sutoto, Sutoto; Abdinagoro, Sri Bramantoro (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
The objective of this research is to examine the connection between hospital performance and customer centricity, focusing on the adoption of Patient-Centered Care (PCC) practices. This study explores how customer-centric approaches influence key performance indicators (KPIs) in healthcare organizations to highlight the benefits of fostering a patient-centered care culture. A mixed-methods approach combines qualitative case studies with quantitative data analysis. Data were collected through questionnaires and interviews with patients, administrators, and healthcare providers from selected hospitals. The quantitative aspect involved statistical analysis of financial performance, readmission rates, and patient satisfaction scores. The qualitative component included in-depth interviews capturing the perspectives of those implementing PCC. Findings reveal a significant positive correlation between hospital performance and customer-centric strategies. Hospitals that actively adopted PCC had lower readmission rates, higher satisfaction scores, and better financial outcomes. Qualitative insights further underscore the importance of organizational culture, staff development, and leadership commitment in successful PCC implementation. The research concludes by offering specific strategies healthcare organizations can adopt to enhance customer-centricity and achieve improved performance outcomes.